Physiological and muscle tissue responses in Litopenaeus vannamei under hypoxic stress via iTRAQ - Chang, Fengtong; Li, Na; Shi, Xiang; Olga, Volovych; Wang, Xiaobing; Diao, Xiaoping; Zhou, Hailong; Tang, Xianming (Frontiers in Physiology, 2022)
White L. vannamei have become the most widely cultivated shrimp species worldwide. Cultivation of L. vannamei is one of the predominant sectors in China’s aquaculture industry. This study focused on the physiological and biochemical responses, differential protein expression, and expression characteristics of the related crucial functional protein genes under low oxygen conditions among different strains of L. vannamei. It was found that 6 h of hypoxic stress caused a significant reduction in the total hemocyte number in both strains, while the hypoxia-sensitive strain showed a stronger reduction. In contrast, the hemocyanin concentration showed only an overall upward trend. Proteomic analysis of L. vannamei muscle tissue revealed 3,417 differential proteins after 12 h of hypoxic stress. Among them, 29 differentially expressed proteins were downregulated and 244 were upregulated in the hypoxia-sensitive strain. In contrast, there were only 10 differentially expressed proteins with a downregulation pattern and 25 with an upregulation pattern in the hypoxia-tolerant strain. Five protein genes that responded significantly to hypoxic stress were selected for quantitative real-time PCR analysis, namely, hemocyanin, chitinase, heat shock protein 90 (HSP 90), programmed death protein, and glycogen phosphorylase. The results showed that the gene expression patterns were consistent with proteomic experimental data except for death protein and glycogen phosphorylase. These results can enrich the general knowledge of hypoxic stress in L. vannamei and the information provided differentially expressed proteins which may be used to assist breeding programs of L. vannamei of new strains with tolerance to hypoxia.